2014
DOI: 10.1002/nau.22671
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of post‐void residual urine

Abstract: Measurement of PVR is recommended in guidelines and recommendations on the management of LUTS and urinary incontinence, but the level of evidence for this measurement is not high. This manuscript summarizes the evidence and provides practice recommendations for teaching purposes in the framework of an ICS teaching module.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(57 citation statements)
references
References 33 publications
0
55
0
2
Order By: Relevance
“…Many authors focus on abnormal PVRVs; however, an internationally accepted definition with clinically significant threshold values is lacking [21]. Although large PVRVs (≥ 200–300 mL) may suggest a higher incidence of lower urinary tract symptoms (LUTS), evidence for using this measurement as a predictor is low [22].…”
Section: Discussionmentioning
confidence: 99%
“…Many authors focus on abnormal PVRVs; however, an internationally accepted definition with clinically significant threshold values is lacking [21]. Although large PVRVs (≥ 200–300 mL) may suggest a higher incidence of lower urinary tract symptoms (LUTS), evidence for using this measurement as a predictor is low [22].…”
Section: Discussionmentioning
confidence: 99%
“…The interval between voiding and PVR measurement should be short [64]. Ultrasound (US) bladder volume measurement is generally the preferred approach for measuring PVR [64], which is not necessarily associated with BOO, since high PVR can be a consequence of BOO and/or poor detrusor function (underactivity) [65,66]. It has been shown that for volumes >50 ml, the diagnostic accuracy of PVR measurement has PPV of 63% and a negative predictive value (NPV) of 52% in determining BOO [62].…”
Section: Post-void Residual Urinementioning
confidence: 99%
“…In general, a PVR volume < 50 mL shows sufficient emptying, while a PVR volume > 200 mL is accepted as inadequate emptying [4]. PVR volume measurement is recommended in individuals with suspected overflow UI, voiding dysfunction, detrusor underactivity, female UI and before starting anticholinergic medication [34]. In conclusion, we cannot exclude the importance of PVR volume measurement based on our results.…”
Section: Discussionmentioning
confidence: 77%